2014
DOI: 10.1038/cdd.2014.193
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of human pancreatic exocrine cells to β-like cells

Abstract: Rodent acinar cells exhibit a remarkable plasticity as they can transdifferentiate to duct-, hepatocyte- and islet β-like cells. We evaluated whether exocrine cells from adult human pancreas can similarly respond to proendocrine stimuli. Exocrine cells from adult human pancreas were transduced directly with lentiviruses expressing activated MAPK (mitogen-activated protein kinase) and STAT3 (signal transducer and activator of transcription 3) and cultured as monolayers or as 3D structures. Expression of STAT3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 37 publications
(58 reference statements)
0
62
0
1
Order By: Relevance
“…Changes in α-cell to β-cell ratios and the appearance of cells positive for both glucagon and insulin have provided some evidence for such conversions; however, in the absence of lineage tracing, direct evidence is still lacking. Other cell types such as pancreatic acinar cells, ductal cells, gall bladder cells, and intestinal cells have also been used to generate insulin-expressing cells, but these cells did not form long-term stable grafts after transplantation, suggesting incomplete cell fate conversion or an unstable epigenetic state 121124 . At this point, the main challenge in translating approach into the clinic is to define reliable methods for efficient production of human β-like cells that can develop stable and functional transplants.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…Changes in α-cell to β-cell ratios and the appearance of cells positive for both glucagon and insulin have provided some evidence for such conversions; however, in the absence of lineage tracing, direct evidence is still lacking. Other cell types such as pancreatic acinar cells, ductal cells, gall bladder cells, and intestinal cells have also been used to generate insulin-expressing cells, but these cells did not form long-term stable grafts after transplantation, suggesting incomplete cell fate conversion or an unstable epigenetic state 121124 . At this point, the main challenge in translating approach into the clinic is to define reliable methods for efficient production of human β-like cells that can develop stable and functional transplants.…”
Section: Strategies To Produce New Endocrine Islet Cellsmentioning
confidence: 99%
“…Recent developments in their work showed the potential to induce NGN3 expression in human exocrine cells by lentiviral-induced overexpression of mitogenactivated protein kinase, and signal transducer and activator of transcription 3 [Lemper et al 2015]. The NGN3-expressing cells entered an endocrine program and specified into functional β cells 42 days after transplantation into normoglycemic immunocompromised mice.…”
Section: In Vitro Reprogramming Of Pancreatic Ductal Cells Into β Cellsmentioning
confidence: 99%
“…The reprogrammed cells can significantly improve the STZ diabetic mice symptoms of hyperglycemia, and insulin secretion can reach 23% of the normal insulin secretion level. Currently, adenoviral vectors have been widely used in the reprogramming system for exogenous gene transfer because of its high transfection efficiency [22][23][24][25][26][27], but still face the risks of integration and immune rejection. Studies have shown that up to 2×10…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of luciferase plasmid by hydrodynamic delivery was assessed by in vivo bioluminescence imaging of luciferase activity using an IVIS Spectrum system (Perkin-Elmer, Waltham, MA) at 3,6,12,24,48, and 72 hours post-injection. Mice were anesthetized with isoflurane, followed by intraperitoneally injection of 150 mg/kg D-luciferin (Goldbio, USA).…”
Section: In Vivo Bioluminescence Imagingmentioning
confidence: 99%